Sovereign screens : Aboriginal media on the Canadian West Coast - Dowell, Kristin L. (University of Nebraska Press, 2013)
While Indigenous media have gained increasing prominence around the world, the vibrant Aboriginal media world on the Canadian West Coast has received little scholarly attention. This ethnography of the Aboriginal media community in Vancouver reveals the various social forces shaping Aboriginal media production, including community media organizations and avant-garde art centers, as well as the national spaces of cultural policy and media institutions. -- Publisher's website.